THE ROLE OF ADULT ENTREPRENEURSHIP EDUCATION FOR POVERTY REDUCTION IN POST COVID– 19 ERA IN NIGERIA - Okenwa-Ojo, Mary; Yusuff, R. O.; Adewole, A. A. (African Journal of Educational Management, 2023)
The study examined the role of adult entrepreneurship education for poverty reduction in post COVID-19 era in Nigeria. It is evident that for a nation like Nigeria to strive better in her education and sustain economy adult entrepreneurship education should be taken into consideration and should be broadly embraced in all level of her education to alleviate poverty. With the reduction of COVID-19 epidemic in Nigeria, towns and villages are trying to cope with the difficulties encountered by the citizens, there is a necessity for people to learn more skills and competencies that would enable them cope in living in such circumstances. Adult entrepreneurship education refers to knowledge, skills and information given to adults to develop, organize and manage business ventures along with any of its risk in order to make profit. The main function of entrepreneurship education among others is to give functional education for the adults and youths that will assist them to be self-employed and self-reliant. It is a key drive to the economy, wealth and a high majority of jobs are created by small businesses established by entrepreneurship-minded individuals, which should lead to big business, which plays a greater role in employment generation and job creation. This paper recommends that the government at all levels should raise awareness about adult entrepreneurship education loan opportunities to adult and non-formal education learners for self-reliance and self-sustenance, to mention a few.